2009
DOI: 10.1002/lt.21747
|View full text |Cite
|
Sign up to set email alerts
|

Early high peak hepatitis C viral load levels independently predict hepatitis C-related liver failure post-liver transplantation

Abstract: The aim of this study was to examine the importance of the serum hepatitis C viral load within the first year post-liver transplant in determining posttransplant survival. A retrospective analysis of 118 consecutive hepatitis C virus-positive liver transplant recipients who received an allograft from January 1997 to September 2005 was undertaken with a median duration of follow-up of 32.4 months. Univariate and multivariate analyses were used to examine the effects of recipient, donor, surgical, and viral fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 34 publications
0
44
3
Order By: Relevance
“…HCV antigen expression by hepatocytes can be detected by week 3 [12,13]. HCV RNA levels at this early time point may correlate with histologic severity and fibrosis progression [14][15][16].…”
Section: Factors That Affect Progression Of Fibrosismentioning
confidence: 97%
“…HCV antigen expression by hepatocytes can be detected by week 3 [12,13]. HCV RNA levels at this early time point may correlate with histologic severity and fibrosis progression [14][15][16].…”
Section: Factors That Affect Progression Of Fibrosismentioning
confidence: 97%
“…16,17 Several reports suggested that viral load before or after transplant did not correlate with the severity of liver disease or predict the timing of HCV recurrence after transplant, but another study showed an association between increased viral titers and worse histologic activity, increased risk of fibrosis, and decreased survival. [17][18][19] Transplant-related factors that may be associated with progression of HCV disease include immunosuppressive treatment. Steroid maintenance therapy has no detrimental effect on graft or patient survival.…”
Section: Factors Associated With Hepatitis C Virus Disease Progressionmentioning
confidence: 99%
“…Progression of graft hepatitis-C seems to be accelerated in patients with HCV-genotype-Ib, high pre-transplant HCV-RNA-load and early post-transplant peak of viremia [29,[35][36][37]. Interestingly, HCVcore protein has been demonstrated to promote inflammation by the release of oxidative stress and to reinforce apoptosis and steatosis.…”
Section: Viral Factorsmentioning
confidence: 99%
“…In spite of low success rates, HCV-infection is treated by subcutaneous administration of 180μg of Peg-IFN-α2a once a week and oral intake of RBV up to three times per day [22,35,81]. The cumulative duration of antiviral treatment comprises 12-18 months.…”
Section: Current Treatment Standardsmentioning
confidence: 99%